2013
DOI: 10.1007/s10683-013-9373-9
|View full text |Cite
|
Sign up to set email alerts
|

Do short-term laboratory experiments provide valid descriptions of long-term economic interactions? A study of Cournot markets

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Another concern of our manipulation is that online data might be of limited quality due to a lower degree of scrutiny compared to the laboratory (Anderhub et al 2001). Recent experimental studies conclude that online-based and lab-based inferences are equally reliable provided that similar procedures are used in both settings (Arechar et al 2018;Hergueux and Jacquemet 2015;Normann et al 2014). As detailed in Appendices A and B of the supplementary material, we invested much effort to address this concern and relied on the same subject pool and similar procedures in both treatments.…”
Section: Limitations Of Our Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Another concern of our manipulation is that online data might be of limited quality due to a lower degree of scrutiny compared to the laboratory (Anderhub et al 2001). Recent experimental studies conclude that online-based and lab-based inferences are equally reliable provided that similar procedures are used in both settings (Arechar et al 2018;Hergueux and Jacquemet 2015;Normann et al 2014). As detailed in Appendices A and B of the supplementary material, we invested much effort to address this concern and relied on the same subject pool and similar procedures in both treatments.…”
Section: Limitations Of Our Studymentioning
confidence: 99%
“… 2018 ; Hergueux and Jacquemet 2015 ; Normann et al. 2014 ). As detailed in Appendices A and B of the supplementary material, we invested much effort to address this concern and relied on the same subject pool and similar procedures in both treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses on the production quantity adjustments and SCR modeled temporal correlation of the decisions (see e.g. Normann et al, 2014;Zwick and Rapoport, 2002) using an AR(p) withinsubject correlation structure, where p denotes the lag index and φ 1 , …, φ p are the parameters to be estimated.…”
Section: Resultsmentioning
confidence: 99%
“…Because the game we use is indefinitely repeated, any outcome that has better payoffs for both players than in the CournotNash equilibrium can be supported as the subgame-perfect equilibrium of the game if the players are patient enough (Schmalensee, 1988). Many experiments with this game have found that the players aim for the symmetric joint-optimum (Huck et al, 2001(Huck et al, , 1999Normann et al, 2014). …”
mentioning
confidence: 99%
“…This is particularly true when comparing prosocial behavior in laboratory tasks to behavior in the real world. Some studies find significant correlations (Camerer ; Dai, Galeotti, and Villeval ; Karlan ; Normann, Requate, and Waichman ), but others report remarkably robust null effects across a wide range of tasks and measures (Carpenter and Seki ; Galizzi and Navarro‐Martinez 2019; Stoop, Noussair, and van Soest ). In many studies that do report a significant relationship, the correlation is often noticeably smaller than test‐retest correlations when an individual completes the same task multiple times.…”
Section: Introductionmentioning
confidence: 99%